The effect of mandibular buccal tilting on the accuracy of posterior mandibular spiral tomographic images: An in vitro study - Mahnaz Sheikhi; Vida Maleki (Wolters Kluwer Medknow Publications, 2011)
Background: Accurate measurement of the height and buccolingual thickness of available bone has a significant role in dental implantology. The shadow of ramus on the mandibular second molar region disturbs the sharpness of conventional tomographic images. The aim of this study was to evaluate the effect of transferring the shadow of ramus from the center of the focal plane, by changing the position of mandible, on the sharpness of the posterior mandibular region. Materials and Methods: In this experimental study, we used 10 dry human mandibles. Three metal balls were mounted on the midline and mandibular second molar regions bilaterally. Standard panoramic and tomographic images were taken. Then, the mandible was tilted buccaly for 8° - compensating the normal lingual inclination of the mandibular ridge and teeth on this region - and tomographic images were taken again. The height and thickness of bone were measured on the images and then compared with the real amounts measured directly on mandibles. Also, the sharpness of mandibular canals was compared between the two tomographic methods. Findings were analyzed with repeated measured ANOVA test (P<0.05). Results: The height of mandibular bone, on the images of the tilted tomography technique was more accurate compared to standard (P<0.001), but standard tomography had more accuracy in estimating the buccolingual thickness at the half-height point. Regarding the sharpness of mandibular canals, we found no significant differences between two tomographic methods. Conclusion: Buccal tilting is recommended when measuring the bone height is more important, but routine standard tomography is preferred when the thickness is requested.